Methicillin-resistant Staphylococcus aureus causing ocular infections in a tertiary care center in north India - Shariq Wadood Khan; Adil Raza; Shaik Mohammed Zakir; Haris Manzoor Khan; Mohammad Shahid (Asian Journal of Medical Sciences, 2022)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is often the cause of serious ocular infections that are difficult to treat, and these ocular infections are a significant public health problem. Aims and Objective: The study aimed to determine the prevalence and antimicrobial susceptibility pattern of MRSA in ocular infections. Materials and Methods: The patients were recruited from the outpatient and inpatient departments from July 2018 to February 2021 from the Institute of Ophthalmology and study was done in the Department of Microbiology, JNMC, AMU, Aligarh (UP). MRSA was identified by Cefoxitin disk diffusion method. Polymerase chain reaction was used for detection of mecA gene. Results: Seventy-six S. aureus were found in 350 patients with clinically suspected various bacterial infections. Among all S. aureus, 41 (53.94%) were MRSA. Maximum 10 (24.4%) MRSA were isolated from lacrimal apparatus infection followed by 7 (17%) in lid infection, and 6 (14.6%) in keratitis. All MRSA isolates were positive for mec A gene. MRSA isolates showed 85.3% sensitivity to amikacin and 100% to vancomycin. Fluoroquinolones showed resistance to the majority of MRSA strains. Conclusion: MRSA is the main pathogen of ocular infections, resistant to a wide range of antibiotics. The monitoring of antibiotic sensitivity patterns, regular surveillance of associated ocular diseases, and strict antibiotics policy should be followed in an institute.